Manajemen Keperawatan Paliatif Pada Pasien HIV/AIDS Dalam Meningkatkan Kepatuhan Terapi Antiretroviral (ARV): Studi Kasus Di Rumah Sakit Umum Kabupaten Empat Lawang - Yanto Suryanto; Berlian Kando Sianipar; Rita S; Atifah Syahputri; Novia Afrini F; Nanda Adelia (Jurnal Multidisiplin Dehasen (MUDE), 2026)
HIV/AIDS is a chronic disease that causes a decline in the immune system and increases the risk of opportunistic infections as well as various physical, psychological, social, and spiritual problems that can affect adherence to antiretroviral (ARV) therapy. To describe the application of palliative nursing management in improving adherence to ARV therapy in HIV/AIDS patients. The study used a descriptive method with a case study approach on Mr. W, 25 years old, diagnosed with HIV/AIDS accompanied by Pulmonary Tuberculosis and suspected Toxoplasma Cerebri at Empat Lawang District Hospital. Data were collected through interviews, observations, physical examinations, and medical record documentation. Nursing problems were found in the form of nutritional deficits, activity intolerance, sleep pattern disturbances, anxiety, spiritual distress, and the risk of non-adherence to ARV therapy. Interventions were carried out through symptom management, health education, therapeutic communication, spiritual support, and family involvement. After the intervention, the patient showed an improvement in physical condition, decreased anxiety, and increased motivation and commitment to ARV therapy. Holistic palliative nursing management can improve adherence to ARV therapy and the quality of life of HIV/AIDS patients.